BRIEF HISTORICAL INFORMATION ABOUT THE CONCEPT OF “VALUES” AND ITS TEACHING AT SCHOOL - Tologozhoeva N. O.; Asanova A. E. (Vestnik Issyk-Kulʹskogo universiteta)
The article analyzes the place of the concept of quantity in the history of mathematics, and notes that teaching mathematics at school plays a major role in the development of functional properties of students' perception, such as attention, abilities, will and, most importantly, thinking. In fact, studying quantities such as length, area, mass, etc., as well as their units of measurement, requires students to observe and analyze in relevant situations, which contributes to the development of their ability to make correct conclusions through measurements. Measuring quantities is closely related to the formation of concepts of numbers, arithmetic operations, and geometric figures in practical activities. The use of historical materials when studying these quantities is also of particular importance. The concept of quantity is one of those concepts that connects mathematics with real life. Therefore, the article attempts to reveal its significance based on historical data, facts, and research that have reached us.